1984
DOI: 10.1177/00220345840630011601
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Emergence of the Deciduous Teeth

Abstract: Exact ages of emergence of the twenty deciduous teeth have been investigated on a longitudinal sample of 195 French-Canadian children (113 boys and 82 girls). A multivariate analysis of variance yielded a significant overall sex difference (p less than 0.0001). It has been found that the emergence of the deciduous dentition in boys is more precocious than that in girls by about one month; this difference is present at the emergence of the upper central incisor and is maintained henceforth. The only notable exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2
3

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 21 publications
2
34
2
3
Order By: Relevance
“…In this study, maxillary and mandibular teeth erupted earlier in boys than in girls with the exception of the first molars (p>0.05) and maxillary second molars (p<0.05). Similar results of earlier eruption of first molars in girls than in boys have been reported (11). Reports of gender differences in the timing of eruption of primary teeth are rison between sexes (Table 3) showed a clear tendency towards earlier eruption in boys for all teeth except maxillary second molar and maxillary and mandibular first molars which erupted earlier in girls.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, maxillary and mandibular teeth erupted earlier in boys than in girls with the exception of the first molars (p>0.05) and maxillary second molars (p<0.05). Similar results of earlier eruption of first molars in girls than in boys have been reported (11). Reports of gender differences in the timing of eruption of primary teeth are rison between sexes (Table 3) showed a clear tendency towards earlier eruption in boys for all teeth except maxillary second molar and maxillary and mandibular first molars which erupted earlier in girls.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, dental formulas are used to estimate biological age and to track children's growth (10). Longitudinal studies provide information on the ages of eruption of individual teeth, along with their variations (4,5,11,12) unclear in the literature (11). Oziegbe et al (16) suggested genetic and molecular studies to confirm the possible association of earlier emergence times of primary teeth to accelerated growth in boys during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…The larger sample and the methodology for collecting the ages of dental emergence have been previously described (Demirjian et al, 1982;Tanguay et al, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…H o w e v e r , a l t h o u g h t h i s m e t h o d i s f a s t , c h e a p a n d n o t v e r y i n f l u e n c e d b y i n t r a -a n d interobserver error, eruption is not a good age indicator when used alone, due to factors like interindividual or populational variation (Garn et al, 1959;Moorees et al, 1963), systemic or local diseases (Ungar, 1937) or the elapsed time without changes (Teivens & Mörnstad, 2001). Numerous authors have investigated the chronology and sequence of eruption in different populations (Foti et al, 2003;Fulton & Price, 1954;Giles et al, 1963;Logan & Kronfield, 1933;Olze et al, 2007;Planells et al, 1993;Saunders et al 1993;Tanguay et al 1984; Van der Linden, 1980). Some of this research examines the correlation between dental eruption and other development parameters; for example Lewis and Garn (Garn & Lewis, 1959) which evaluates parameters such as somatic and sexual growth, personality and state of health, or Green (Green, 1961) which attempts to establish correlations between dental, skeletal and chronological age and weight and height, finding a stronger correlation between dental and chronological age even than that existing between dental and bone development.…”
Section: Dental Eruptionmentioning
confidence: 99%